The Zone in Reverse - Francesco Sebregondi (Footprint)
This essay proposes a reconstruction of the problem of logistics as seen through the prism of Gaza. Questioning the common approach of logistics strictly in terms of the flows that it releases and speeds up, it argues that the Gaza blockade itself constitutes a vast logistical operation. The essay proceeds by setting Gaza’s architecture of confinement against the ‘architecture of flow’ that typically characterises logistical sites around the world. By underlining the material connections between these, the essay calls for an approach of processes of restriction of mobility as a mirror image of the fast-tracking operations that logistics is primarily known for. On this basis, it proposes a notion of logistical power as a mode of power specifically exerted through the production of a differential regime of mobility.